KEPUASAN PASIEN PULANG PADA REKONSILIASI OBAT DENGAN PEMANFAATAN SISTEM INFORMASI DI RS HERMINA PANDANARAN SEMARANG - Suwarni, Sri (Jurnal Farmasi Sains dan Teknologi, 2024)
The importance of public health development according to the Health Act of 2023 requires efforts to manage services to improve health status and community satisfaction. These efforts include services in hospitals, one of the pharmaceutical services is drug reconciliation to reduce the incidence of duplication or drug interactions. Information system implementation is a tool to facilitate patient data documentation. This study aims to determine patient satisfaction at discharge on drug reconciliation with the utilization of information systems at Hermina Pandanaran Hospital Semarang. The research method is a triangulation survey using primary data from questionnaire sheets and interviews then secondary data review of reconciliation procedures, prospective data. The reconciliation depth interview process is carried out on clinical pharmacists who use information systems. The results of the study are the level of patient satisfaction can be reflected in reliability (Reliability) 3.90, direct evidence (Tangible) 3.90, responsiveness (Responsivness) 3.89, assurance (Assurance) 3.94, and empathy (Emphaty) 3.88. The mean satisfaction is 3.90, 96.90% of patients are satisfied with drug information services at discharge. Discharge patients who received reconciliation drug information services were satisfied with the drug information received, due to the support of the speed of access to information using the information system. Although there is no special information system for drug reconciliation, it is facilitated in SIMRS for accessibility of drug reconciliation data so that pharmaceutical personnel can provide information quickly to patients discharged at Hermina Pandanaran Hospital Semarang..